The Influence of Authentic Leadership and Employee Well-Being on Happiness at Work, Exhaustion, and Individual Performance at Yoi Kona Coffee & Space Surabaya - Hindami, Moh Argy Hariran; Slamet Riyadi; Sumiati (International Journal of Economics (IJEC), 2025)
This study aims to determine the influence of Authentic Leadership and Employee Well- Being on Happiness at Work, Exhaustion, and Individual Performance in Yoi Kona Coffee and Space Surabaya. This study was quantitative in nature. The analysis tool used is The Structural Equation Model (SEM) data analysis method using the Warp PLS 3.0. The sample consisted of 70 respondents using a saturated sample. The results of this study indicated that Authentic Leadership had no significant effect on Exhaustion. Authentic Leadership has a significant effect on Happiness at Work. Authentic Leadership had a significant effect on Individual Performance. Employee Well-Being has a significant effect on Exhaustion. Employee Well-Being has a significant effect on Happiness at Work. Employee Well-Being has a significant effect on Individual Performance. Happiness at Work significantly affects Individual Performance. Exhaustion has a significant effect on Individual Performance